2011
DOI: 10.17221/131/2010-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the spatio-temporal expression of insecticidal genes in cotton

Abstract: Abstract:The most significant breakthrough in plant biotechnology is the development of the techniques to transform genes from unrelated sources into commercially important crop plants to develop resistance against targeted insect pests. The spatio-temporal expression of insecticidal genes in transgenic cotton varies with plant age, plant parts and environmental conditions. The understanding of this temporal and spatial variation in efficacy and the resulting mechanisms is essential for cotton protection and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The expression of transgenes in our lines varied in different generations. These results are in agreement with previous studies conducted by Wu et al (2002), Mahon et al (2002), Xia et al (2005), Adamczyk et al (2009 and Bakhsh et al (2011Bakhsh et al ( , 2012 who have reported inconsistency in insecticidal gene expression over the crop growth period and in various generations. However, investigation at molecular, genetic, as well as physiological levels should help in understanding the differential expression of transgenes and the quantitative changes in insecticidal proteins in insect resistant cotton plants.…”
Section: Fourth and Fifth Generationsupporting
confidence: 93%
“…The expression of transgenes in our lines varied in different generations. These results are in agreement with previous studies conducted by Wu et al (2002), Mahon et al (2002), Xia et al (2005), Adamczyk et al (2009 and Bakhsh et al (2011Bakhsh et al ( , 2012 who have reported inconsistency in insecticidal gene expression over the crop growth period and in various generations. However, investigation at molecular, genetic, as well as physiological levels should help in understanding the differential expression of transgenes and the quantitative changes in insecticidal proteins in insect resistant cotton plants.…”
Section: Fourth and Fifth Generationsupporting
confidence: 93%
“…Mendelian inheritance of foreign genes in transgenic plants has been observed in alfalfa (Micallef et al, 1995), rice (Duan et al, 1996), maize (Fearing et al, 1997), cotton (Canming et al, 2000;Zhang et al, 2000;Xia et al, 2007;Zhang et al, 2007;Daud et al, 2009;Bakhsh, 2010) and cowpea (Ivo et al, 2008). However in some cases, incorporated gene exhibited distorted Mendelian segregation pattern (Spencer et al, 1992;Wan and Lemaux, 1994;Somers et al, 1994;Altman et al, 1996;Wu et al, 2002;Rashid et al, 2008;Bakhsh, 2010 Bakhsh et al (2010Bakhsh et al ( , 2011Bakhsh et al ( , 2012. There are many worth considering factors that can contribute variation in gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal variations affect the transgene expression in different cotton lines. This variation for the transgene efficacy is correlated with the promoter activity 47,48 . The other factors reported for variation www.scienceasia.org in the level of gene expression, might be alteration in nucleotide sequence, gene integration point, copy number, cellular changes, and environmental factors 21,49 .…”
Section: Effect Of Drought Stress On Yieldmentioning
confidence: 98%